Efek Pemberian Campuran Madu Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Hamil Dengan Anemia - Endry Sulistyowati; Sri Mintarsih; Sulastri Sulastri; Hanantya Henry Setyabudi (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2023)
Background: Anemia in pregnant women can increase the risk of premature birth, maternal and child mortality, and infectious diseases. According to WHO, the prevalence of anemia in pregnant women is around 35-75%, and it increases with the growth of gestational age. Objective: This study aims to increase insight and knowledge and to find out the incidence of pregnant women with anemia before and after the intervention. In addition, to analyze the effect of giving a mixture of honey to increase hemoglobin levels in anemic pregnant women. Methods: The design in this study used the Quasi-experimental design method. Quasi-experimental design (quasi-experimental) with a quantitative approach to one group design pre-test and post-test. The population in this study were all pregnant women who came to check their pregnancy at the Pratama Hidayah Clinic in January 2022. The sampling technique in this study was purposive sampling, namely taking samples based on considerations with the desired elements by inclusion criteria with the number of a sample of 15 respondents. Results: Test using the Shapiro Wilk method. The significance value of the pre-test variable is 0.994 and the significance value of the post-test variable is 0.153 or > 0.050, meaning that the data in this study are normally distributed. So the statistical test used is the T-test with a p-value of pre-test - post test of 0.000 < 0.050. Thus, it can be concluded that there is a significant difference between the average pre-test and post-test variables. This means that there is an effect of giving a mixture of honey increases hemoglobin levels in pregnant women with anemia. Conclusion: From the research conducted that there is a significant difference between the value of the pre-test and post-test, besides that there is a very strong relationship between the effect of giving a mixture of honey to the increase in hemoglobin levels in the mother. pregnant with anemia.